Influence of Pore Fluid on Grain‐Scale Interactions and Mobility of Granular Flows of Differing Volume. Issue 12 (2nd December 2022) - Taylor‐Noonan, Alexander M.; Bowman, Elisabeth T.; McArdell, Brian W.; Kaitna, Roland; McElwaine, Jim N.; Take, W. Andy
Abstract: The presence of a pore fluid is recognized to significantly increase the mobility of saturated over dry granular flows. However, the mechanisms through which pore fluid increases mobility may not be captured in experimental flows of small volume typical of laboratory conditions. Here we present the results of dry and initially fluid saturated or "wet" experimental flows of near‐monodisperse coarse‐grained ceramic particles in a large laboratory flume for five source volumes of 0.2–1.0 m 3 . Measurements include flow height, velocity profile, pore pressure, and evolving solid volume fraction, as well as the final deposit shape. The dry experiments constrain the frictional properties of the common granular material and comparison with wet flows permits an independent evaluation of the interstitial fluid effects. These results demonstrate that flow dilation and strong variation in the velocity profile are directly linked to a greatly increased mobility for wet granular flows compared to dry, and a significant influence of scale as controlled by source volume on flow behavior. Excess pore pressure need not be present for these effects to occur. Plain Language Summary: An accurate prediction of how fast and how far a landslide, such as a debris flow, will travel is essential to define the hazard posed to life and property by these geophysical flows. While dry frictional flows often behave according to the simple physics of friction resisting motion, initially water saturated granular flows tend to travel farther and faster than the same scenario under dry conditions. In this paper, we explore this phenomenon in detail, using comparatively large‐sized monodisperse grains, in which we expect the pore fluid effects to be limited to buoyancy. We undertake high‐speed video analysis to examine differences in grain‐scale behavior that might lead to increased mobility in saturated over dry flows, and scan the deposit shape to quantify how far the debris travels. Large flume tests comparing dry versus saturated flows for five source volumes of 0.2–1.0 cubic meters reveal that, in contrast to dry flows, saturated flows travel significantly farther as the volume of the landslide increases. This occurs even while the pore fluid pressure acts only to provide buoyancy in the flow. This data is unique as it will enable researchers to test how well numerical simulations are able to model the travel behavior of the same material in a dry and water saturated state. Key Points: Dry granular flows of five volumes between 0.2 and 1.0 m 3 observed to yield a constant effective friction in flume tests Saturated flows of the same granular material exhibited a nonlinear decrease in effective friction with increasing volume Results provide unique test scenario for simulations by constraining friction properties prior to exploring pore fluid effects